2019
DOI: 10.1038/s41467-019-09698-6
|View full text |Cite
|
Sign up to set email alerts
|

Origin of band gaps in 3d perovskite oxides

Abstract: With their broad range of properties, ABO 3 transition metal perovskite oxides have long served as a platform for device applications and as a testing bed for different condensed matter theories. Their insulating character and structural distortions are often ascribed to dynamical electronic correlations within a universal, symmetry-conserving paradigm. This view restricts predictive theory to complex computational schemes, going beyond density functional theory (DFT). Here, we show that… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
157
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 198 publications
(168 citation statements)
references
References 74 publications
(139 reference statements)
10
157
1
Order By: Relevance
“…The discussion on polymorphous networks in cubic halide perovskites focuses on positional polymorphism. There is also spin polymorphism (ie different local spin environments) noted earlier for electronic spin in paramagnetic 3d oxide 60,61 and in the paraelectric electronic polarization 62,63 . The polymorphous cubic phases apply also to oxides that have dynamically unstable phonons, as shown in Fig.…”
Section: Not Only In Halide Perovskitesmentioning
confidence: 63%
“…The discussion on polymorphous networks in cubic halide perovskites focuses on positional polymorphism. There is also spin polymorphism (ie different local spin environments) noted earlier for electronic spin in paramagnetic 3d oxide 60,61 and in the paraelectric electronic polarization 62,63 . The polymorphous cubic phases apply also to oxides that have dynamically unstable phonons, as shown in Fig.…”
Section: Not Only In Halide Perovskitesmentioning
confidence: 63%
“…(h) JT distortions as well as semiclassical size effect distortions can contribute to the opening of band gaps in Mott insulators. We have previously identified 33 We conclude that the electronically-induced Jahn-Teller distortion mode Q2and the geometrically induced steric Q2 + octahedral deformation mode are fully captured by a static mean-field method. This is in line with recent theoretical works that have demonstrated that static mean-field methods capable of inducing broken symmetry such as Density Functional Theory 13,26,30,33 in a polymorphous representation suffice to also explain (i) the trends in gapping and type of magnetic order across the ternary ABO3 series 33…”
Section: A Landau-esque Perturbation Approachmentioning
confidence: 65%
“…52 In line with this result, recent SCAN-based studies obtain band gaps in the high-temperature cuprates and 3d transition-metal perovskite oxides in accord with experimental observations. 37,38,40,53 This enables us to avoid the GW quasiparticle corrections and use directly the generalized Kohn-Sham band energies as the eigenvalues of the electrons (E ck+Q ) and holes (E vk ) in the BSE Hamiltonian, where only seven conduction and seven valence bands were considered. Figure 1(a) and 1(c) show the electronic band structure (blue lines) and crystal structure of La 2 CuO 4 in the LTO structure for the antiferromagnetic (AFM) phase.…”
Section: Computational Methodologymentioning
confidence: 99%